Right to Health Care: The Practice of the ECTHR and the Case of Ukraine - Yaroshenko, Oleg; Steshenko, Volodymyr; Tarasov, Oleh; Nurullaiev, Ilkin; Shvartseva, Mariia (The Age of Human Rights Journal, 2022)
The relevance of the research topic is due to the importance of human rights in a democratic society. Despite the fact that all natural human rights are important, the right to health care is practically in the forefront, because without its observance all other rights are leveled. Moreover, the relevance of the topic is even greater given the fact that for a long time the relevant law was not given due attention in law or in legal science. The right to health care is comprehensive and includes other human rights that derive from it. The existing case law of the European Court of Human Rights (ECtHR) confirms the importance of the human right to health care. In its judgments, the Court emphasizes the importance of this right and reaffirms the need for States to monitor its observance. The aim of the study – analysis of international legal norms and standards, as well as the practice of the ECtHR in the context of the human right to health. The leading research method used in the article is the formal-legal method, the application of which provided an effective analysis of the legal framework of international law, national legislation of Ukraine, and the case law of the ECtHR. Which, in turn, allowed to determine the importance of human rights to health and places of relevant law in the practice of the ECtHR. The article analyzes the theoretical and legal approaches to understanding the right to health care and on this basis identifies the place of relevant law in the human rights system and its main determinants. The case law of the European Court of Human Rights is analyzed and the main articles of the European Convention on Human Rights (ECHR), which the applicants applied for in violation of the right to health care, are identified. The analysis of the case law of the ECtHR provided an opportunity to identify existing shortcomings in the legislation of the member states. Based on this, it is possible to understand and distinguish ways to solve problems and methods for eliminating such violations in the future. The practical significance of the article lies in the analysis of the case law of the European Court of Human Rights, the separation of rights related to the right to protection of life, as well as the identification of the main determinants of the studied law.